Enhanced and stabilized photoluminescence of perovskite cesium lead bromide nanocubes through ordered assemblies. Issue 9 (17th April 2023) - Sasaki, Moeka; Hashimoto, Shota; Iso, Yoshiki; Oaki, Yuya; Isobe, Tetsuhiko; Imai, Hiroaki
Abstract : The quantum yield of photoluminescence and the photostability of perovskite cesium lead bromide nanocubes were improved by the formation of two-dimensional ordered arrays on a substrate. Abstract : This work clarified the effects of self-assembly of perovskite cesium lead bromide (CsPbBr3 ) nanocubes (NCs) covered with didodecyldimethyl ammonium bromide (DDAB) on photoluminescence (PL) properties. Although the PL intensity of isolated NCs was weakened in the solid state even under inert conditions, the quantum yield of PL (PLQY) and the photostability of DDAB-covered NCs were drastically improved by the formation of two-dimensional (2D) ordered arrays on a substrate. The PLQY of the 2D arrays increased to ca. 60% by initial excitation illumination at 468 nm and was maintained for over 4000 h. The improved PL properties are attributable to the fixation of the surface ligand around the NCs in the specific ordered arrays.